Growing up hard in Harlan County - Jones, G. C. (Green C.), 1913- (University Press of Kentucky, 1985)
G.C. ""Red"" Jones's classic memoir of growing up in rural eastern Kentucky during the Depression is a story of courage, persistence, and eventual triumph. His priceless and detailed recollections of hardscrabble farming, of the impact of Prohibition on an individualistic people, of the community-destroying mine wars of ""Bloody Harlan, "" and of the drastic dislocations brought by World War II are essential to understanding this seminal era in Appalachian history